A poesia épica na construção dos Discursos de Dion Crisóstomo - Rossi, Andrea Lúcia Dorini de Oliveira Carvalho [UNESP] (Universidade Estadual de Maringa, 2010)
Epic poetry in the construction of Dion Chrysostom’s Discourses. The construction of images in the speeches of Dion Chrysostom was drawn from references in Homer. When the orator uses images from Greek epic poetry, Dion Chrysostom intimates the representation of images found in the literature to propagate his philosophical and political ideas during the first century A.D. under the administration of the emperors Domitian, Nerva and Trajan. Current analysis of the author’s works discusses literature as one of the representational forms of Hellenistic identity under Roman domination.

Ao elaborar os seus Discursos, Dion Crisóstomo se vale das referências constantes de Homero para a construção de imagens. Ao usar as imagens presentes na poesia épica grega, Dion Crisóstomo evoca as representações imagéticas presentes na literatura para difundir suas ideias filosóficas e políticas durante o final do Século I d.C sob os governos de Domiciano, Nerva e Trajano. Ao se fazer a análise desse autor, pretende-se também discutir a literatura como uma das formas de representação da identidade helenística sob o Principado Romano.
Keywords: Epic poetry; Myths; Hellenism; Roman dominion; Dion Chrysostom; Poesia épica; Mitos; Helenismo; Principado Romano; Dion Crisóstomo